2019
DOI: 10.1177/0894439319828012
|View full text |Cite
|
Sign up to set email alerts
|

Explaining Online News Engagement Based on Browsing Behavior: Creatures of Habit?

Abstract: Understanding how citizens keep themselves informed about current affairs is crucial for a functioning democracy. Extant research suggests that in an increasingly fragmented digital news environment, search engines and social media platforms promote more incidental, but potentially more shallow modes of engagement with news compared to the act of routinely accessing a news organization’s website. In this study, we examine classic predictors of news consumption to explain the preference for three modes of news … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
70
0
8

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(93 citation statements)
references
References 40 publications
(43 reference statements)
0
70
0
8
Order By: Relevance
“…The resulting levels are "Low education," "Intermediate education," and "High education." In line with theories of attitude polarization and selective exposure, people with more extreme ideological leanings might be more prone to engage in selective exposure (Fawzi 2019;Möller et al 2019). Political extremism could also be correlated with populist attitudes, which are a phenomenon that goes beyond left and right ideological leanings ( Van Hauwaert and Van Kessel 2018).…”
Section: Discussionmentioning
confidence: 77%
“…The resulting levels are "Low education," "Intermediate education," and "High education." In line with theories of attitude polarization and selective exposure, people with more extreme ideological leanings might be more prone to engage in selective exposure (Fawzi 2019;Möller et al 2019). Political extremism could also be correlated with populist attitudes, which are a phenomenon that goes beyond left and right ideological leanings ( Van Hauwaert and Van Kessel 2018).…”
Section: Discussionmentioning
confidence: 77%
“…For example, one study showed that SNS users consumed almost twice the number of news outlets in the previous week as did nonusers (2). Similar results emerged regarding the use of web aggregators (portals) and search engines, although people may use search engines in a more goal-driven fashion compared to SNS (1).…”
mentioning
confidence: 87%
“…news exposure | online media use | web tracking data P eople can come across news and other internet offerings in a variety of ways, for example, by visiting their favorite websites, using search engines, or following recommendations from contacts on social media (1). These routes do not necessarily lead people to the same venues.…”
mentioning
confidence: 99%
“…Consequently, Google has been named the most important online source of (political) information by German online users (Stark, Magin, & Jürgens, 2017). Furthermore, informational search engine queries were found to be the most common gateway to online news in a recent tracking study of Dutch online users (Möller, van de Velde, Merten, & Puschmann, 2019). Thus, search engines may be considered a decisive factor in political opinion formation and, subsequently, voting intentions.…”
Section: Use Of Search Engines In Political Information and Voting Bementioning
confidence: 99%